A Future Look - Eduardo Mario DIAS; Eduardo FACCHINI; Antônio Carlos DE MORAES; Mauricio LIMA FERREIRA; Willian REGINATO ESTE; Maria Lídia Rebello PINHO DIAS (Advances in Distributed Computing and Artificial Intelligence Journal, 2015)
Since the Industrial Revolution, some believe that the machines will take the place of men, their simplest task to the most sophisticated. Others, that technology has transformed the habits of society and improves his quality of life. This article debates the technology and its relationship with the man, the automation of human occupations and the impact on their daily lives. Although the issue travels in the realm of science fiction, the man faces specifically with the machine in carrying out their professional activities, in meeting their reproductive needs, including entertainment. To address this issue, it was essential to recover the debate on the Law of Declining Trend Profit formulated by Karl Marx in Capital Rate and illustrates, recover the work of Isaac Asimov's fiction, I, Robot.